The Analysis of Determining Credit Worthiness Using Weighted Product and SMART Methods in SPB Cooperatives - Ai Ilah - Warnilah; Intan Nurul Hawa; Yani Sri Mulyani (Indonesian Journal of Information Systems, 2020)
The Savings and Loan Cooperative of Simpeunan Pameungkeut Banda is a cooperative that has been established in Tasikmalaya. The system of lending currently used at Simpeunan Pameungkeut Banda Cooperative is still manual, so the management requires quite a long time. Besides that, the cooperative has not had a system that supports in determining the credit worthiness decision. Thus, the credit is not on target, because it does not fit the specified criteria. For this reason, the writers were to make a research on the comparison of weighted product and smart methods in determining credit worthiness in Pameungkeut Banda Cooperative. The purpose of research was to determine who were eligible and who were not eligible to get the credit given the criteria that have been determined using the Weighted Product method and SMART methods. The results of the analysis using the Weighted Product method obtained the highest value of 0.067 and the lowest value of 0.032, while SMART method obtained the highest value of 79.2 and the lowest value of 25. The results show that SMART method is more effective in determining credit worthiness.